Contours of value capture :India's neoliberal path of industrial development - Roy, Satyaki (New Yrok University Printing House, 2020)
"The delinking of growth and employment and stagnation in manufacturing together with rising share of services in both output and employment had been a major concern in the context of industrialising India. Policy debates in the past three decades have been confined to binaries such as public versus private, manufacturing versus services, production versus finance or inward versus outward looking strategies. These are important choices in strategizing industrialisation. Contours of Value Capture highlights how these immediate choices are influenced by class process of accumulation. It foregrounds 'value capture' as the critical concept in analysing accumulation in the realm of production and finance articulated through exploitation, expropriation and exclusion. It discusses how India and other developing countries figure in global production networks, the asymmetric distribution of gains, how financialization creeps into India's corporate sector, although not always similar to advanced countries, manifest a reification of 'objectivity' that helps in reproducing capital relations. It takes capital as an integral relation and aims to analyse the complex causal relationship between apparently disparate trends such as stagnation in productive investment, rising financial profits, declining share of wages, informality, self-employment and dispossession. Contesting the ideological view that economies are neutral containers and economic transactions are powerless exchanges between equally placed agents, it sees power and hegemonic discourse as constitutive of the world of production and finance realised through hierarchies of capital and architecture of institutions. These norms and institutions normalise expropriation and legitimise exclusion. This book discusses how power and profit explains the making and unmaking of the neoliberal path of industrialisation in India"--
Includes bibliographical references and index.
Keywords: Industrialization; Manufacturing industries; Service industries